Assignment 18

#$&*

course Mth 174

7/31 10

......!!!!!!!!...................................

Calculus II

Asst # 18

 

 

*********************************************

Question: 

  ****   Query   problem 11.3.4  (as 10.3.6) Euler y' = x^3-y^3, (0,0), `dx =.2, 5 steps

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 y` = x^3 - y^3

Starting point = (0,0)

x y delta y = (m) * delta x

————————————————

0 0 0 = (0) (.2)

.2 0 .0016 = (.008)(.2)

.4 .0016 .0144 = (.064)(.2)

.6 .0144 .0432 = (.216)(.2)

.8 .0576 .16 = (.512)(.2)

y(1) = 0.16

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

 3

.............................................

Given Solution:

  ****   what is your estimate of y(1)?

 

 

** The table below summarizes the calculation.  x values starting at 0 and changing by `dx = .2 are as indicated in the x column.  y value starts at 0.

 

The y ' is found by evaluating x^3 - y^3.  `dy = y ' * `dx and the new y is the previous value of y plus the change `dy.

 

Starting from (0,0):

 

m = 0, delta y = 0.2*0 = 0, new point (0.2,0)

m = 0.2^3 = 0.008, delta y = 0.2*.008 = 0.0016, new point (0.4, 0.0016)

m = 0.4^3 - 0.0016^3 = 0.064, delta y = 0.2*0.064 = 0.0128, new point (0.6, 0.0144)

m = 0.6^3 - 0.0144^3 = 0.216, delta y = 0.2*0.216 = 0.0432, new point (0.8,0.0576)

m = 0.8^3 - 0.0576^3 = 0.512, delta y = 0.2*0.512 = 0.1024, new point (1.0, 0.16)

y(1) = 0.16

......!!!!!!!!...................................

                                                  11:35:35

......!!!!!!!!...................................

  ****   Describe how the given slope field is consistent with your step-by-step results.

......!!!!!!!!...................................

                                                  11:35:53

I'm not sure exactly what you are asking here

 

** If you follow the slope field starting at x = 0 and move to the right until you reach x = 1 your graph will at first remain almost flat, consistent with the fact that the values in the Euler approximation don't reach .1 until x has exceeded .6, then rise more and more quickly.  The contributions of the first three intervals are small, then get progressively larger.

.........................................

                                                  11:35:53

......!!!!!!!!...................................

  ****   Is your approximation an overestimate or an underestimate, and what

property of the slope field allows you to answer this question?

......!!!!!!!!...................................

                                                  11:36:07

An underestimate

 

** The slope field is rising and concave up, so that the slope at the left-hand endpoint will be less than the slope at any other point of a given interval.  It follows that an approximation based on slope at the left-hand endpoint of each interval will be an underestimate. **

.........................................

                                                  11:36:07

......!!!!!!!!...................................

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 OK

 

 

------------------------------------------------

Self-critique Rating:

 OK

*********************************************

Question: 

  ****   Query   problem 11.3.13 4th and 3d editions 11.3.10 (formerly 10.3.10)  Euler and left Riemann sums, y' = f(x), y(0) = 0

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

 Euler and the left Riemann sums use the same formula of dy =y`* dx over the interval.

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

 3

.............................................

Given Solution:

  ****   explain why Euler's Method gives the same result as the left Riemann sum for the integral

......!!!!!!!!...................................

     

 

 Euler's method multiplies the value of y ' at the left-hand endpoint of each subinterval to calculate the approximate change dy in y, using the approximation dy = y ' * `dx.  This result is calculated for each interval and the changes dy are added to approximate the total change in y over the interval.

 

The left-hand Riemann sum for y ' is obtained by calculating y ' at the left-hand endpoint of each subinterval then multiplying that value by `dx to get the area y ' `dx of the corresponding rectangle.  These areas are added to get the total area over the large interval.

 

So both ways we are totaling the same y ' `dx results, obtaining identical final answers.

 

 

.........................................

                                                  11:36:36

......!!!!!!!!...................................

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 OK

 

 

------------------------------------------------

Self-critique Rating:

 OK

*********************************************

Question: 

  ****   Query problem 11.4.19 (3d edition 11.4.16 previously 10.4.10)  dB/dt + 2B = 50, B(1) = 100

 

  ****   what is your solution to the problem?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

dB/dt = 50 - 2 B

dB / (50 - 2B) = dt

 

Take the integral of both sides:

 

-.5 ln|50 - 2B| = t + c

ln | 50 - 2B | = -2 (t + c) 

| 50 - 2B | = e^(-2(t+c))

B(1) = 100 and t = 1

50 - 2B = -150

|50 - 2 B | = 2 B - 50

2B - 50 = e^(-2(t+c))

B = 25 + .5 * e^(-2(t+c))

 

B(1) = 100 so:

 

100 = 25 + .5 * e^(-2 ( 1 + c) )

e^(-2 ( 1 + c) ) = 150

-2(1+c) = ln(150)

c = -1/2 * ln(150) - 1

 

B(1) = 25 + 75 e^2 e^(-2 * 1)

= 25 + 75 e^0 = 25 + 75 = 100

| 50 - 2B | = e^(-2(t+c))

| 50 - 2B | = e^(-2c) * e^(-2 t)

Replace e^(-2c) with C:

| 50 - 2B | = C e^(-2 t)

50 - 2 B = + - C e^(-2 t)

B = 25 + C e^(-2t)

B(1) = 100 = 25 + C e^(-2)

C = 75 e^2

B = 25 + 75 e^-2 e^(-2t) 

Simplified:

B = 25 + 75 e^(-2(t - 1) )

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

 3

.............................................

Given Solution:

 

 ** We can separate variables.

We get dB/dt = 50 - 2 B, so that dB / (50 - 2B) = dt.

 

Integrating both sides we obtain

 

-.5 ln(50 - 2B) = t + c, where c is an arbitrary integration constant.

 

This rearranges to

 

ln | 50 - 2B | = -2 (t + c)  so that

| 50 - 2B | = e^(-2(t+c)).  Since B(1) = 100 we have, for t = 1, 50 - 2B =

-150 so that |50 - 2 B | = 2 B - 50.  Thus

2B - 50 = e^(-2(t+c)) and

B = 25 + .5 * e^(-2(t+c)). 

 

If B(1) = 100 we have

 

100 = 25 + .5 * e^(-2 ( 1 + c) ) so that

e^(-2 ( 1 + c) ) = 150 and

-2(1+c) = ln(150).  Solving for c we find that

c = -1/2 * ln(150) - 1.

 

Note that this checks out: 

 

B(1) = 25 + 75 e^2 e^(-2 * 1)

= 25 + 75 e^0 = 25 + 75 = 100. 

 

Note also that starting with the expression

 

| 50 - 2B | = e^(-2(t+c)) we can write

| 50 - 2B | = e^(-2c) * e^(-2 t).  Since e^(-2c) can be any positive number we replace this factor by C, with the provision that C > 0.   This gives us

 

| 50 - 2B | = C e^(-2 t) so that

 

50 - 2 B = +- C e^(-2 t), giving us solutions

 

B = 25 + C e^(-2t) and

B = 25 - C e^(-2t).

 

The first solution gives us B values in excess of 25; the second gives B values less than 25.

 

Since B(1) = 100, the first form of the solution applies and we have

 

100 = 25 + C e^(-2), which is easily solved to give

C = 75 e^2.

 

The solution corresponding to the given initial condition is therefore

 

B = 25 + 75 e^-2 e^(-2t),  which is simplified to give us

 

B = 25 + 75 e^(-2(t - 1) ). ** 

 

 

.........................................

                                                  11:36:54

......!!!!!!!!...................................

  ****   What is the general solution to the differential equation?

......!!!!!!!!...................................

                                                  11:37:08

I'm not sure, I didn't find a general solution

.........................................

                                                  11:37:08

......!!!!!!!!...................................

  ****   Explain how you separated the variables for the problem.

......!!!!!!!!...................................

                                                  11:37:28

I just treated db and dt as normal variables and multiplied dt times the

entire equation

.........................................

                                                  11:37:28

......!!!!!!!!...................................

  ****   What did you get when you integrated the separated equation?

......!!!!!!!!...................................

                                                  11:37:40

1/2B = 25t - B*t

.........................................

                                                  11:37:41

......!!!!!!!!...................................

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 OK

 

 

------------------------------------------------

Self-critique Rating:

 OK

*********************************************

Question: 

  ****   Query problem 11.4.40 was 11.4.39 (was 10.4.30) t dx/dt = (1 + 2 ln t ) tan x,

1st quadrant

 

  ****   what is your solution to the problem?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

t dx/dt = (1 + 2 ln t ) tan x

x = arcsin(A*t^(ln(t) + 1))

 

t dx/dt = (1 + 2 ln t)

dx / (tan x) = (1 + 2 ln t) / t * dt

= 1/t dt + 2 ln(t) / t * dt

cos x / sin x * dx =  1/t dt + 2 ln(t) / t * dt .

 

Integrate both sides which gives us:

 

ln(sin(x)) = ln(t) + ( ln(t) )^2 + c

sin(x) = e^(ln(t) + (ln(t))^2 + c)

= e^(ln(t)) * e^((ln(t))^2) * e^c

= A t e^((ln(t))^2)

x = arcsin(A t e^(ln(t)^2)

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

 3

.............................................

Given Solution:

 

x = arcsin(A*t^(ln(t) + 1))

 

** We separate variables.

 

t dx/dt = (1 + 2 ln t) tan x is rearranged to give

dx / (tan x)

= (1 + 2 ln t) / t * dt

= 1/t dt + 2 ln(t) / t * dt or

 

cos x / sin x * dx =  1/t dt + 2 ln(t) / t * dt .

 

Integrating both sides

 

On the left  we let u = sin(x), obtaining du / u with antiderivative ln u =

ln(sin(x))

 

Thus our antiderivative of the left-hand side is ln(sin(x)).

 

On the right-hand side 1/t dt + 2 ln(t) / t * dt  we first find an antiderivative of ln(t) / t

 

Letting u = ln(t) we have du = 1/t dt so our integral becomes int(u^2 du) = u^2 / 2 = (ln(t))^2 / 2.

 

Thus integrating the term 2 ln(t) / t we get (ln(t))^2.

 

The other term on the right-hand side is easily integrated:    int(1/t * dt) = ln(t).

 

Our equation therefore becomes

 

  ln(sin(x)) = ln(t) + ( ln(t) )^2 + c so that

 

  sin(x) = e^(ln(t) + (ln(t))^2 + c)

= e^(ln(t)) * e^((ln(t))^2) * e^c

= A t e^((ln(t))^2).

 

where A = e^c is an arbitrary positive constant (A = e^c, which can be any positive number)

 

so that

 

x = arcsin(A t e^(ln(t)^2)

This makes sense for t > 0, which gives a real value of ln(t), as long as t e^(ln(t)^2 < = 1 (the domain of the arcsin function is the interval [ -1, 1 ] ).

 

 

  **

.........................................

                                                  11:38:09

......!!!!!!!!...................................

  ****   What is the general solution to the differential equation?

......!!!!!!!!...................................

                                                  11:38:18

The same thing

.........................................

                                                  11:38:18

......!!!!!!!!...................................

  ****   Explain how you separated the variables for the problem.

......!!!!!!!!...................................

                                                  11:38:38

I multiplied dt by the entire equation and treated it as a normal variable

.........................................

                                                  11:38:38

......!!!!!!!!...................................

  ****   What did you get when you integrated the separated equation?

......!!!!!!!!...................................

                                                  11:39:05

ln|sin(x)| =(2 ln(t) + 1)^2/4

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 OK

 

 

------------------------------------------------

Self-critique Rating:

OK"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

OK"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#This looks good. Let me know if you have any questions. &#